POD-1/TCF21 Reduces SHP Expression, Affecting LRH-1 Regulation and Cell Cycle Balance in Adrenocortical and Hepatocarcinoma Tumor Cells - França, Monica Malheiros (Biomed Res Int, 2015)
POD-1/TCF21 may play a crucial role in adrenal and gonadal homeostasis and represses Sf-1/SF-1 expression in adrenocortical tumor cells. SF-1 and LRH-1 are members of the Fzt-F1 subfamily of nuclear receptors. LRH-1 is involved in several biological processes, and both LRH-1 and its repressor SHP are involved in many types of cancer. In order to assess whether POD-1 can regulate LRH-1 via the same mechanism that regulates SF-1, we analyzed the endogenous mRNA levels of POD-1, SHP, and LRH-1 in hepatocarcinoma and adrenocortical tumor cells using qRT-PCR. Hereafter, these tumor cells were transiently transfected with pCMVMycPod-1, and the effect of POD-1 overexpression on E-box elements in the LRH-1 and SHP promoter region were analyzed by ChIP assay. Also, Cyclin E1 protein expression was analyzed to detect cell cycle progression. We found that POD-1 overexpression significantly decreased SHP/SHP mRNA and protein levels through POD-1 binding to the E-box sequence in the SHP promoter. Decreased SHP expression affected LRH-1 regulation and increased Cyclin E1. These findings show that POD-1/TCF21 regulates SF-1 and LRH-1 by distinct mechanisms, contributing to the understanding of POD-1 involvement and its mechanisms of action in adrenal and liver tumorigenesis, which could lead to the discovery of relevant biomarkers.